Root caries prevalence and severity in Brazilian adults and older people - Marques, Regina Auxiliadora de Amorim; Antunes, Jose Leopoldo Ferreira; Sousa, Maria da Luz Rosario; Peres, Marco Aurelio; Frazao, Paulo (Revista de Saúde Pública, 2013)
OBJECTIVE: To estimate the prevalence of root caries in Brazilian adults and elderly. METHODS: We assessed data from the Brazilian Oral Health Survey (SBBrasil 2010). Dental examinations were performed on 9,564 adults and 7,509 elderly individuals in households in the 26 state capitals, the Federal District and 150 provincial towns. Diagnostic criteria and data assessment tools were those standardized by the World Health Organization. The outcome was measured by using root caries index and the index of decayed and filled dental roots. RESULTS: The prevalence of root caries was 16.7% in adults and 13.6% in the elderly. The index of decayed and filled dental roots was 0.42 and 0.32 for adults and the elderly respectively, with most of the index represented by untreated caries. The prevalence of root caries differed significantly among states capitals and provincial towns, with higher values being reported in the state capitals in the North and Northeastern Brazilian regions. In adults, the root caries index ranged from 1.4% in Aracaju to 15.1% in Salvador (both in the Northeast). Among the elderly, this index ranged from 3.5% in Porto Velho to 29.9% in Palmas (both North). Root caries was more prevalent in men than in women in both age groups. CONCLUSIONS: There is a wide variation in root caries indices in adults and in the elderly, and between and within Brazilian regions. Most root caries is untreated. We recommend the incorporation of this disease into the oral health surveillance system.